Emotional Intelligence Scale for International Students: A Proposal for a Developed Version - AL-Qadri, Abdo Hasan; Zhao, Wei; Li, Miao; Al-khresheh, Mohammad; Boudouaia, Azzeddine (Frontiers in Education, 2022)
Assessing Emotional Intelligence (EI) may someday be considered more vital than testing IQ. In higher education, making international students aware of their EI could improve emotional awareness, adaptability, and functioning, thereby assisting in day-to-day interactions and adapting to life in a foreign country. Incorporating an Emotional Intelligence Scale (EIS) could aid in the onboarding of international students.Researchers aimed to develop and validate an EIS capable of accurately measuring EI amongst international students attending a teaching university in Northwest China. The target population included male and female undergraduate and graduate-level students, ranging in age from 18-40. 482 individuals participated. Past studies showed EI could be measured using an EIS; therefore, this study sought to develop an appropriate scale to validate such findings in the target population.The multivariate statistical technique used for data reduction, or factor analysis, was both exploratory and confirmatory and the Scale factor models were adjusted, as appropriate, based on the modification indexes. The outcomes showed that the 24-item and supported EIS models, including four-factor models, had appropriate indices.The four factors considered were Understanding and Regulation, Positive Affect, Optimism, and Utilization. Techniques employed to ensure the reliability of the EIS, included Cronbach's alpha coefficient, test/re-test stability, CR, and AVE.Findings indicated that the EIS might effectively be employed to measure EI in this target population. Of interest, there were no statistically significant differences between post-graduate/graduate students or different genders.